Depression during Pregnancy and Preeclampsia in third Trimester in Women Attending Prenatal Care Center of Esfahan in 2010-2012 - Mahshid Moeinimehr; Azam Foroghipour; Sabihe Shokrani; Shadi Goli; Bahram Soleymani (Golestan University of Medical Sciences, 2015)
Background and Objective: Depression and preeclampsia have an effect on both mother and fetus. Hence, we aimed to assess depression during pregnancy and preeclampsia in third trimester of pregnancy. Material and Methods: This cohort Study was conducted on 966 pregnant women, who were multigravida and 18-35 years, referring to three prenatal care centers. Using convenience sampling, the data was collected by Patient Health Questionaire-9 and analyzed by chi square, Mann-Whitney, Logistic Regression. Results: Of 966, 70.1% were depressed and 29.9% were not depressed. The relationship between depression and preeclampsia was significant (P=0.017, adgusted OR=2.99). In 9.32 percent of preeclamptic patients, 91.68 suffered from mild depression in 8.33 percent of them, 91.67% from moderate depression and in 33.33 percent of the preeclamptic patients, 66.67 % suffered from moderate-severe depression. Conclusion: Given that dpression may lead to preeclampsia and the intensity of depression is related to preeclampsia, early recognition and treatment of depressed women can be helpful in the management of preeclampsia.